Recording cilia activity in ctenophores: effects of nitric oxide and low molecular weight transmitters - Norekian, Tigran P.; Moroz, Leonid L. (Frontiers in Neuroscience, 2023)
Cilia are the major effectors in Ctenophores, but very little is known about their transmitter control and integration. Here, we present a simple protocol to monitor and quantify cilia activity in semi-intact preparations and provide evidence for polysynaptic control of cilia coordination in ctenophores. Next, we screen the effects of several classical bilaterian neurotransmitters (acetylcholine, dopamine, L-DOPA, serotonin, octopamine, histamine, gamma-aminobutyric acid (GABA), L-aspartate, L-glutamate, glycine), neuropeptides (FMRFamide), and nitric oxide (NO) on cilia beating in Pleurobrachia bachei and Bolinopsis infundibulum. Only NO inhibited cilia beating, whereas other tested transmitters were ineffective. These findings further suggest that ctenophore-specific neuropeptides could be major candidate signaling molecules controlling cilia activity in representatives of this early-branching metazoan lineage.